Comparative study of steristrips and subcuticular suture for wound closure after thyroid surgery - G., Vinay; K. S., Balasubrahmanya (International Surgery Journal, 2017)
Background: Any skin closure technique aims at opposing the skin edges precisely without tension for sufficient time to allow healing to take place. The ease and speed with which the skin closure is completed, the level of patient discomfort, the complication rate, and the final cosmetic result are the factors which has to be considered in making a comparison of different types of wound closure. This study aims at comparing steristrips and subcuticular sutures for wound closure after thyroid surgery based on assessment of post-operative pain, neck mobility and cosmetic appearance. Methods: A comparative study was carried out among 90 subjects attending Department of Surgery, K. R. Hospital, Mysuru over a period of 10 months. Subjects of either sex undergoing thyroidectomy will be randomized to had their wounds closed by steristrips or subcuticular sutures using a simple randomization table. Patients who underwent previous neck irradiations, secondary neck surgeries, and patients with poor compliance were excluded from the study. Descriptive statistics, unpaired t-test and chi-square test were used to analyse the results. Results: The mean age group of the study subjects was 48.6 (range 24-76) years. The gender distribution showed a higher number of females (82) as compared to males (8). 70 patients were diagnosed with multinodular goitre, 16 patients were of thyroid neoplasms and 4 were of inflammatory thyroid conditions. 12 patients underwent subtotal thyroidectomy and 78 patients underwent total thyroidectomy. Wound closure by steristrips had less post-operative pain, acceptable neck mobility and excellent scar appearance as compared to subcuticular sutures. Conclusions: The choice of materials for wound closure will depend on the surgeon's preference. However, this study does show that steristrips sutures can be removed more quickly and is more acceptable method of wound closure as compared to subcuticular sutures after thyroid surgery.